Tributes to Dick Ohmann: Special Session, Modern Language Association, January 7, 2022 - Chinn, Sarah; Entin, Joseph; Foley, Barbara; Keeton, Pat; Lauter, Paul; O'Malley, Susan; Schrecker, Ellen (Radical Teacher, 2022)
Seven friends and colleagues remember Richard Ohmann.